Queer theory: Under construction - Dilley, Patrick (International Journal of Qualitative Studies in Education, 1999)
This article outlines how the concepts of queer and queer theory have been applied to qualitative studies. The multiple definitions of queer are examined, to foster an understanding of the positions from which theorists have utilized the concept to examine a number of disciplines. The advancement of the tenets of queer theory is outlined chronologically, to display the evolution of the theory through intradisciplinary applications. The body of qualitative works utilizing queer theory is categorized (language, literature, and arts; history; life histories / life stories; and queer theory as praxis) and juxtaposed. In addition, efforts to define and enact a "queer pedagogy" are analyzed. Suggestions for further application of queer theory in education, ethnography, and qualitative studies conclude the article.
Keywords: approches et analyses; discipline; discours dominant; ethnographie; histoire et politique; hétérosexisme; pédagogie; pédagogie queer; queer; ressource en ligne; sciences de l'éducation; systèmes d'oppressions; thématiques; éducation; étude qualitative